The balance sheet channel of monetary policy transmission: Evidence from Nigeria - Olorunsola E. Olowofeso; Abiodun S. Bada; Kufre J. Bassey; Kumafan S. Dzaan (CBN Journal of Applied Statistics, 2014)
This paper assesses the existence of a balance sheet channel of monetary policy transmission in Nigeria by examining whether variation in the official interest rate, with respect to the 2007- 2008 global financial crisis, feeds through to the deposit money banks (DMBs) balance sheets, and ultimately reflects in output and prices. Using quarterly macroeconomic data and stock from 2002 to 2012, the study employs an ordinary least squares (OLS) and autoregressive (VAR) framework to investigate the linkages between policy, DMB balance sheet, output and price. The results reveal the existence of a balance sheet channel in Nigeria with a significant impact of DMBs balance sheet composition on output growth and price. However, output and price did not react homogeneously to changes in monetary policy variations due to the global financial crisis.
Keywords: E31; E44; E52; E58; 330; Balance sheets Channel; Deposit Money Bank; Financial Crisis; Monetary Policy; Output; Price